A synthesis of soybean yield response to controlled drainage under varying precipitation patterns in the US Midwest - J.S. Strock; M.A. Youssef; H. Moursi; K. Nelson; A.Z. Ranaivoson; C.A. Poole (Agricultural Water Management)
Controlled drainage (CD) is a valuable management practice for improving water quality and reducing drainage water discharge volume from agricultural fields, but its specific impact on soybean [Glycine max (L.) Merr.] productivity is not well understood. The objectives of this study were to examine the regional effect of CD on soybean grain yield compared to free drainage (FD), investigate factors affecting soybean yield response to CD, and provide guidance for management of CD to optimize soybean yield. This synthesis included 31 site-years of data collected from 11 field sites in six U.S. Midwestern states during 2007–2018 where soybean was planted under FD and CD. On average, there was no statistically significant difference in soybean grain yield between FD (3915 kg ha−1) and CD (3900 kg ha−1). However, 35 % of the dataset indicated that CD either increased or decreased soybean yield by 4 % or more compared to FD. Additional analysis was conducted on a subset of 11 site-years of data to assess underlying factors (i.e., drainage system design and management, and weather conditions during the growing season) affecting soybean yield response to CD. This analysis revealed that CD successfully alleviated plant stress caused by mild to moderate drought resulting in increased soybean grain yield by 4–8 % in six site-years. In contrast, CD reduced soybean grain yield by 4–9 % in five site-years during wetter growing seasons. Variability in growing season precipitation coupled with management of CD were the key determinants of soybean grain yield response to CD. The timing and length of wet and dry periods influenced the severity of crop stress and yield loss as soybean sensitivity to wet and dry conditions varies for different growth phases. The management of the CD system could either exacerbate or alleviate stresses caused by wet and dry conditions. Based on results of this synthesis, guidelines were developed for managing manually operated CD systems in the U.S. Midwest to optimize soybean yield response to CD by maximizing positive effects during dry periods while limiting negative effects of the practice during wet periods of the growing season.